Cultural Conservation Through Javanese Traditional Pambiwara Course on The Role of a Sanggar Permadani in Sukoharjo Regency, Central Java - Marimin; Wijaya Mahendra; Hilmi Pujihartati Sri; Sudarsana (E3S Web of Conferences)
The Sukoharjo Sanggar Permadani has a strategic role in carrying out the conservation and cultivation of the Javanese language. The role of the pambiwara or master of ceremonies (MC) in Javanese customs which requires pambiwara to be proficient in Javanese, especially “inggil” manners. The role of the studio is important in providing training to individuals who are interested in becoming pambiwara so that they are able to speak Javanese manners well and to maintain cultural existence as well as becoming a professional job. This research found that the Sanggar Permadani has the role of: (1) Concrete actions to preserve language enhance the capacity for good communication, fostering cooperation among farmer communities. (2) Enculturation Javanese Culture in Solo Residency, which is also predominantly rural. (3) Transforming the sanggar non-commercial entity aimed at maintaining social bonds and solidarity, ultilizing leisure time for discussions on collaborative efforts in land management, seed propagation, fertilizer procurement, and rice pest control. (4). The activities of the sanggar serve as a driving to revitalize and preserve the essence of the Javanese language within society.